Co-injection of Bile and Indocyanine Green for Detecting Pancreaticobiliary Maljunction of Choledochal Cyst - Onishi, Shun; Yamada, Koji; Murakami, Masakazu; Kedoin, Chihiro; Muto, Mitsuru; Ieiri, Satoshi (European Journal of Pediatric Surgery Reports, 2022)
The usage of near-infrared (NIR) fluorescence imaging with indocyanine green (ICG) has gained popularity in many procedures in pediatric surgery. ICG generates fluorescent light only when it combines with a protein. We herein report a novel technique for detecting pancreaticobiliary maljunction (PBMJ) with co-injection of bile and ICG in laparoscopic choledochal cyst resection and hepaticojejunostomy for a pediatric patient. A 4-year-old girl presented with abdominal pain and intermittent vomiting. Enhanced computed tomography and magnetic resonance cholangiopancreatography showed a 17-mm type Ia choledochal cyst. Definitive PBMJ was not detected preoperatively. Laparoscopic choledochal cyst resection and hepaticojejunostomy were performed using five ports. A percutaneous silicon catheter was inserted into the gallbladder, and bile juice was aspirated. The amylase level of the bile juice was over 3 × 105 IU/L. The aspirated bile juice and ICG were mixed and co-injected into the gallbladder through the catheter. ICG combined with protein in bile juice and generated fluorescent light. Dilated common bile duct and pancreas were detected by NIR fluorescence imaging. This imaging technique was helpful for detecting the dissection margin of the distal side of the choledochal cyst inside the pancreatic tissue and preventing injury of the pancreatic tissue. This is the first case of ICG application for laparoscopic choledochal cyst resection in a pediatric patient. After resection of the choledochal cyst, laparoscopic hepaticojejunostomy was completely performed. Our technique is a safe and low-invasive method of detecting and excising the distal side of the cyst without a risk of radiography and residual bile duct.
Keywords: indocyanine green; pancreaticobiliary maljunction; choledochal cyst; near-infrared fluorescence imaging; laparoscopic surgery